2021
DOI: 10.3389/fphys.2021.672252
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Myocardial Mitochondria Structural and Functional Phenotype in a Murine Model of Diabetic Cardiomyopathy

Abstract: People affected by diabetes are at an increased risk of developing heart failure than their non-diabetic counterparts, attributed in part to a distinct cardiac pathology termed diabetic cardiomyopathy. Mitochondrial dysfunction and excess reactive oxygen species (ROS) have been implicated in a range of diabetic complications and are a common feature of the diabetic heart. In this study, we sought to characterise impairments in mitochondrial structure and function in a recently described experimental mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…However, since RCR was increased indicating uncoupling, mitochondrial respiration is inefficient and does not result in higher ATP generation [ 28 , 49 ]. In contrast, Parker et al reported a decrease in succinate-linked OXPHOS in diabetic rat hearts [ 50 ]. Similarly, other authors have found that heart mitochondrial respiration is impaired in diabetic rats, presenting reduced NADH-linked OXPHOS, OXPHOS capacity and decreased ET capacity [ 51 , 52 , 53 , 54 ].…”
Section: Effects Of Diabetes On Mitochondrial Respiration In Animal S...mentioning
confidence: 99%
“…However, since RCR was increased indicating uncoupling, mitochondrial respiration is inefficient and does not result in higher ATP generation [ 28 , 49 ]. In contrast, Parker et al reported a decrease in succinate-linked OXPHOS in diabetic rat hearts [ 50 ]. Similarly, other authors have found that heart mitochondrial respiration is impaired in diabetic rats, presenting reduced NADH-linked OXPHOS, OXPHOS capacity and decreased ET capacity [ 51 , 52 , 53 , 54 ].…”
Section: Effects Of Diabetes On Mitochondrial Respiration In Animal S...mentioning
confidence: 99%
“…Mitochondrial dysfunction and oxidative stress are largely involved in the cellular senescence process observed in malignant neoplasms, aging, and different neurodegenerative and cardiovascular diseases [2]. Although heart failure is multi-factorial, some studies have described an increased risk in diabetic patients, even after therapeutic control measures and prophylaxis for coronary artery disease and hypertension [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have shown that the interaction of genetic variants and environmental factors contribute to the increasing status of metabolic syndromes [16,17]. Several lines of evidence have indicated the roles of oxidative stress and mitochondrial dysfunction in the pathogenesis of aging, including age-related metabolic and neurodegenerative diseases [1,3,9,[18][19][20][21]. However, the basic mechanisms underlying the pathogenesis of metabolic syndromes and cardiovascular complications remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the activity of SIRT1, a crucial regulator of FA metabolism, was decreased, confirming its important role in cardiac metabolic adaptations via FAO modulation [ 82 ]. In the later stages, more severe effects of DMC appeared, for instance, STZ-induced DM mice on HFD for 26 weeks had increased myocardial fibrosis and LV diastolic dysfunction, elevated LV superoxide levels, decreased mitochondria area, increased levels of mitochondrial complex III, and complex V protein abundance, while reducing complex II oxygen consumption [ 83 ].…”
Section: Mitochondrial Energy Metabolism In Dcmmentioning
confidence: 99%